DEVELOPMENT OF PV AND BESS INFRASTRUCTURE IN INDONESIAN MICROGRID SYSTEM - Maulana, Rinaldi
Indonesia, the largest archipelago country in the world, faces both challenges and opportunities in the energy sector. The country is currently transitioning from using fossil fuels to adopting renewable energy sources like solar, wind, and hydropower. As part of this transformation, multiple microgrids have been erected around the country's islands. However, the process of integrating these fluctuating renewable sources into the power system is complex. This study investigates the progress of hybrid microgrid systems, which are essential for achieving a state of zero net emissions and maximizing energy efficiency and adaptability. Hybrid systems, which combine renewable energy and traditional sources, are essential. The study categorizes microgrids based on their supply patterns, specifically emphasizing isolated and interconnected multiple-microgrid systems. The thesis investigates the expansion, operation, and management of microgrids, as well as their impact on the overall supply side of opration, by analyzing real-life examples. Indonesia is advancing in demand response programs and interconnection operation scenario to the decreasing costs of photovoltaic (PV) systems and batteries. This thesis focuses on the potential for enhancing the expansion and operation of microgrids in Indonesia, with a particular emphasis on creating a sustainable energy future.